Unconditional Prenatal Income Supplement and Birth Outcomes. Issue 10 (October 2016) - Brownell, Marni D.; Chartier, Mariette J.; Nickel, Nathan C.; Chateau, Dan; Martens, Patricia J.; Sarkar, Joykrishna; Burland, Elaine; Jutte, Douglas P.; Taylor, Carole; Santos, Robert G.; Katz, Alan
Abstract : (Abstracted from Pediatrics 2016;137(6):e20152992) The prenatal period is an important period that impacts newborn and lifelong health; exposure to stress, poor nutrition, or substance abuse during this period leads to adverse birth outcomes, including low birth weight and preterm birth. Several initiatives across the world that utilize conditional cash or food transfer include Oportunidades (Mexico), Bolsa Familia Program (Brazil), and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC, United States) have been undertaken to improve prenatal health and birth outcomes.